Efektivitas model pembelajaran kooperatif tipe TGT (Teams Games Tounament) untuk meningkatkan hasil belajar siswa kelas VII di MTs Nabil Husein Samarinda - Marajo, Marajo; Mustamin, Mustamin; Haque, Arina Ilma (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
The purpose of this study was to determine how the effect of using animation movies on the understanding of Qowaid Shorof of class XII students of the Department of Religion at Madrasah Aliyah Negeri 2 Samarinda. This research is a quantitative research. The sampling technique in this study was a saturated sample, namely the entire population was used as a sample, namely 44 students of class XII Department of Religion at MAN 2 Samarinda. The research instruments used in this study were questionnaires filled out by students and also the results of students' test scores. Based on the results of data analysis using the Chi Square formula (x2hit) = 27.47 then consulted with the price (x2tab), at the 5% significance level with db = 4, namely at the 5% significance level (x2tab) = 9.4887. This shows that (x2hit) is greater than (x2tab). Thus, Ha is accepted and H0 is rejected. So it can be seen that there is an effect of using animation movies on Shorof's understanding of class XII students of the Department of Religion at Madrasah Aliyah Negeri 2 Samarinda.